Postactivation potentiation for Muay Thai kicking performance - Brown, L.; Doyle, G.; Bruce-Low, S.; Domingos, S.; Anthony, K.; Rowan, F.; Galbraith, A. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to investigate the effects of postactivation potentiation (PAP) on Muay Thai kicking performance based on 3 different rest intervals. Aiming to quantify and indicate timing protocols for conditioning coaches when training athletes using PAP. 17 male (25.3 ± 3.6 years old; 179.3 ± 2.3 cm; 78.0 ± 5.2 kg), experienced Muay Thai fighters completed a standardized warm-up, including a 10-minute cycle on the Wattbike at 60 watts and 30 body mass squats for a dynamic stretch. Subjects then completed a baseline test by striking a PowerKube using the roundhouse and Teep kick techniques. PAP exercise consisted of 4 squat repetitions to maximum effort, followed by a rest period of 2, 5, or 8 minutes. Subjects then struck the PowerKube again using the roundhouse and Teep kick techniques. Rest periods were presented in a randomized order on separate days, with 72 hours between conditions. The level of significance was set at a = 0.05. Significant increases in both roundhouse (chi2(3) = 38.51, p < 0.05) and Teep kick (chi2(3) = 26.33, p < 0.05) striking power were observed when compared with baseline. For the roundhouse kick, significant differences and large effect sizes were present between all conditions except baseline and 2-minute rest. For the Teep kick, significant differences and large effect sizes were present between baseline and 5-minute rest and baseline and 8-minute rest. This indicates that PAP with 5- or 8-minute rest increased roundhouse and Teep kick power. This research reports that a PAP stimulus from a 4RM squat exercise, followed by a 5- or 8-minute rest period, enhances kick power in trained Muay Thai fighters. This technique provides a readily available, time-efficient method to enhance performance that can be built into the warm-up procedure of athletes before training or competition.